Pelatihan Digital Marketing untuk Meningkatkan Pemasaran Produk UMKM Ikan Asin - Unung Lesmanah; Oktriza Melfazen; Cepi Yazirin (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2023)
In modern era, Digital Marketing has developed rapidly since the use of the internet is high. This is in balance with the development of smartphones which are increasingly reaching all groups, from teenagers to the elderly. However, amidst the development of smartphones, it is not balanced with good use. This happened to the people of Mlaten village, sub-district. Rolling over Pasuruan. The majority of village people have smartphones which can be used as a medium for sales if they can use it. Their daily income depends on selling salted fish which they process themselves. Sales are carried out in traditional markets at prices that are relatively competitive with each other. This service activity is carried out using direct counseling and training methods to utilize digital marketing as a medium for marketing salted fish products. As a result of this service, people can understand the importance of digital marketing in product marketing and people can use digital marketing as a media for marketing their products.